Dimensions of Adversity, Physiological Reactivity, and Externalizing Psychopathology in Adolescence: Deprivation and Threat. Issue 2 (February 2017) - Busso, Daniel S.; McLaughlin, Katie A.; Sheridan, Margaret A.
ABSTRACT: Objective: Dysregulation of autonomic nervous system and hypothalamic-pituitary-adrenal (HPA) axis function is a putative intermediate phenotype linking childhood adversity (CA) with later psychopathology. However, associations of CAs with autonomic nervous system and HPA-axis function vary widely across studies. Here, we test a novel conceptual model discriminating between distinct forms of CA (deprivation and threat) and examine their independent associations with physiological reactivity and psychopathology. Methods: Adolescents ( N = 169; mean [SD] age, 14.9 [1.4] years) with a range of interpersonal violence (e.g., maltreatment, community violence) and poverty exposure participated in the Trier Social Stress test (TSST). During the TSST, electrocardiogram, impedance cardiograph, salivary cortisol, and dehydroepiandrosterone-sulfate data were collected. We compared the associations of poverty (an indicator of deprivation) and interpersonal violence (an indicator of threat) on sympathetic, parasympathetic, and HPA-axis reactivity to the TSST, and assessed whether these differences mediated the association of adversity with internalizing and externalizing symptoms. Results: Exposure to poverty and interpersonal violence was associated with psychopathology. Interpersonal violence, adjusting for poverty, was associated with blunted sympathetic (b = 1.44, p = .050) and HPA-axis reactivity (b = −.09; p = .021). Blunted cortisol reactivity mediated the association of interpersonal violence with externalizing, but not internalizing, psychopathology. In contrast, poverty was not associated with physiological reactivity after adjusting for interpersonal violence. Conclusions: We provide evidence for distinct neurobiological mechanisms through which adversity related to poverty and interpersonal violence is associated with psychopathology in adolescence. Distinguishing distinct pathways through which adversity influences mental health has implications for preventive interventions targeting youths exposed to childhood adversity.